In-situ Corrosion Measurements of WWII Shipwrecks in Chuuk Lagoon, Quantification of Decay Mechanisms and Rates of Deterioration - MacLeod, Ian D. (Frontiers in Marine Science, 2016)
This paper is based on a series of measurements taken on WWII historic shipwrecks that resulted from the effects of Operation Hailstone in February 1944 on the Japanese merchant fleet which was assembled in Chuuk lagoon, Federated States of Micronesia. More than 65 shipwrecks and 250 aircraft were sunk during two main bombing raids. The vessels lost covered a wide range of underwater orientation and water depths and so provided a perfect suite of corrosion experiments. Since the fuel on board the aircraft was either readily burnt at the time or was lost through volatilisation, the wrecked planes present no pollution problems today. However the bunker fuel kept inside on-board storage tanks does present a real conservation management crisis. In-situ measurements on many vessels have determined how water depth, the localised wreck topography, dissolved oxygen levels, temperature and salinity affects the corrosion rate of cast iron and mild steel. Thus corrosion rates can be calculated with confidence.